The right as an instrument of domination of patriarchy in Ecuador - Valle Franco, Alex Iván (2019)
This article its main purpose is to show a historical, theoretical and comparative journey of patriarchy, the use of law as a tool to strengthen it and the struggle of women in the socio-juridical field to reinvindicate their bodies as political territory of autonomous decisions and not dominated. The present investigation is des-criptive and makes use of the qualitative approach and the legal dogmatic way. As a main conclusion, it is determined that despite the social struggles carried out in favor of women's rights, patriarchy does not allow the full reinvindication of wo-men as a full subject of rights, especially a limitation in the exercise of reproducti-ve rights and sexual. The scope of this work excludes the quantitative approach gi-ven that there is difficulty in accessing reliable statistical data from a public health entity in Ecuador.